Google Trends and Indonesia Presidential Elections 2024: Predictor of Popularity Candidate in Digital Age - Abdullah, Assyari; Yazid, Yasril; Jayus, Jayus; Sumaiyah, Sumaiyah; Khairi, Akmal; Edison, Edison; Astuti, Dwi Sutri (Politicon : Jurnal Ilmu Politik, 2024)
Google Trends is an alternative and effective tool for predicting candidate popularity and election results with a simple method. This research aims to analyze and compare the popularity of Indonesia's 2024 presidential candidates using Google Trends. This research uses Google Trends as a tool. Data is taken from December 2022-December 2023 with the keywords 'Anies Baswedan', 'Ganjar Pranowo', and 'Prabowo Subianto. Crowed data is visualized using facilities provided by Google Trends, Canva and Â Flourish Studio's Data Visualization Software with three focus analyses: Interest over time, Interest by Region, and Related queries. The findings of this research show that the trend of searching for information about Indonesia's 2024 presidential candidates has been crowded since October 2022 and increased significantly until December 2023. The popularity of Anies Baswedan and Ganjar Pranowo on Google Trends was the same when each candidate made a declaration. Anies gained full popularity with 100 achievements, as well as Ganjar Pranowo gained full popularity when declared by Megawati Soekarno Putri with 100 achievements. However, the facts were very much different on the day when the Gerinda Party declared Prabowo Subianto. Prabowo's popularity when measured by Google Trends is only perched at position 30 while other candidates are above Prabowo, namely Ganjar 100 and Anies 78. Prabowo's popularity rose on August 13, 2022, which managed to get 100, Anies rose to 79 and Ganjar dropped to 57 even though it was only one day apart. These three candidates have different voter bases in the 2024 presidential election. Anies Baswedan's searchers on Google Trends are spread almost throughout the province. While Ganjar Pranowo excelled in Central Java, while West Papua, Maluku and Sulawesi many wanted to know Prabowo Subianto's information.